Occurrence and Conservation Threats of the Endangered Indian Softshell Turtle (Nilssonia hurum) in the Kankai River and Adjacent Wetlands of Eastern Nepal - Kharel, Milan; Subba, Asmit (Himalayan Journal of Science and Technology, 2024)
Nilssonia hurum (Gray, 1831), an endangered Indian softshell turtle, faces increasing threats due to habitat degradation and direct human exploitation. This study, conducted from October 2023 to September 2024 in the Kankai River and its adjacent wetlands in eastern Nepal, to document species occurrence and assessed conservation threats using community-based surveys. The species showed a high probability of occurrence (Ψ = 0.71 ± 0.05 SE) which was significantly and negatively correlated with the Human  Disturbance Index (HDI = 0.29; β = −1.2, p < 0.05), indicating that even moderate human activity adversely affects its distribution. Major threats identified included sand mining, macroplastic accumulation, and wetland encroachment. The physicochemical parameters, including dissolved oxygen(10.4 ± 2.95 mg/L), pH (8.37 ± 0.31) and temperature (21.95 ± 1.49°C) were within the optimal ranges for freshwater turtles. Field data and perceptions from local stakeholders also confirmed a declining turtle population, with habitat loss cited as the predominant threat. Conservation measures such as regulated sand extraction, pond restoration, and public awareness campaigns are urgently recommended to safeguard remaining populations.